Prevalence and Associated Factors of Sexually Transmitted Infection among Female Sexual Assault Victims attending the Police General Hospital - Nampeng, Parichart; Suthaporn, Sutham (Thai Journal of Obstetrics and Gynaecology, 2025)
Objectives: To assess the prevalence of sexually transmitted infections (STIs) and identify factors associated with STIs among female sexual assault victims. Materials and Methods: A retrospective analysis of medical records for sexual assault victims at the Police General Hospital was conducted over the period from January 2018 to December 2022. Results: Among 1,006 female victims, 12.33% tested positive for at least one STI, with Chlamydia trachomatis (6.66%) and Neisseria gonorrhoeae (2.88%) being the most common. Notably, chlamydia positivity dramatically increased in 2022, while other infections, including syphilis, hepatitis B & C, human immunodeficiency virus have shown minor variations over the years. The 10–19 age group, the largest demographic, had the highest STI prevalence (14.54%). Multivariate analysis identified pyuria as a strong independent predictor of STIs (adjusted odds ratio 4.85, p < 0.001) Conclusion: STIs are prevalent among younger female victims, with Chlamydia trachomatis being the most common. Pyuria were strongly associated with STI risk, with routine urinalysis serving as a valuable diagnostic clue.